2009
DOI: 10.1590/s0100-72032009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Causas do retardo na confirmação diagnóstica de lesões mamárias em mulheres atendidas em um centro de referência do Sistema Único de Saúde no Rio de Janeiro

Abstract: The results of this study suggest that efforts must be made to reduce the time needed to get an appointment with a doctor and to confirm a diagnosis of suspicious lesions, as well as to educate physicians and the women themselves regarding the importance of breast symptoms and the value of prompt evaluation, diagnosis, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
2
36

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 14 publications
7
46
2
36
Order By: Relevance
“…[8][9][10] A percentage of 63.3% of Caucasian women was identified in this study, which is similar to information provided by the Brazilian Institute of Geography and Statistics (IBGE) regarding the Census in 2010, in which 47.7% of the population self-reported being Caucasian. 11 According to statistics concerning female breast cancer provided by the American Cancer Society in the United States, various rates of incidence were identified according to race/ethnicity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[8][9][10] A percentage of 63.3% of Caucasian women was identified in this study, which is similar to information provided by the Brazilian Institute of Geography and Statistics (IBGE) regarding the Census in 2010, in which 47.7% of the population self-reported being Caucasian. 11 According to statistics concerning female breast cancer provided by the American Cancer Society in the United States, various rates of incidence were identified according to race/ethnicity.…”
Section: Discussionsupporting
confidence: 83%
“…These results show the need to reduce the rate of diagnoses in advanced stages by reducing the time required to establish diagnoses, and by providing access to timely screening and treatment. 8 In regard to survival rates, this study identified that 77.3% of the population survived the five-year period. A study conducted in Paraíba, Brazil with 438 patients reported that 79.1% of the population survived five years.…”
Section: Discussionmentioning
confidence: 94%
“…Esse aspecto tem sido estudado por diversos autores que ponderam que o impacto desse fator está consideravelmente atrelado às possibilidades de acesso ao diagnós-tico e ao tratamento 18,27,28,29 . Publicações brasileiras que analisaram os fatores relacionados às disparidades no acesso à mamografia e ao retardo na confirmação diagnóstica em estados localizados nessas regiões, encontraram resultados distintos com relação à variável 19,33 . Em Teresina (Piauí), as mulheres que se autorreferiram como negras e pardas tinham menor chance de ter realizado mamografia se comparadas às brancas (p = 0,03) 33 .…”
Section: Resultsunclassified
“…25 Furthermore, the delay in confirming the diagnosis of breast lesions in women attending a SUS reference center was observed in another study, and that was associated with the presence of symptoms, the long interval between the onset of symptoms and the first assessment, and between onset of symptoms and diagnostic confirmation. 26 In a study on trends in breast cancer mortality in Mexico between 1980 and 2009 regional disparities were observed. It was noted that, although the number of deaths from this cause had gradually increased over time nationwide, in some states of the country this increase was extremely significant.…”
Section: Discussionmentioning
confidence: 99%